Mini review: Individual differences and domain-general mechanisms in object recognition - Gauthier, Isabel; Cha, Oakyoon; Chang, Ting-Yun (Frontiers in Cognition, 2022)
Over the past three decades, object recognition moved away from domain-general questions, favoring investigation of putative category-specific mechanisms. But growing interest in individual differences in object recognition is putting the spotlight back on domain-general mechanisms, supporting their existence rather than simply assuming them. We reflect on the relative progress in three areas of visual cognition—visual object recognition, ensemble perception, and holistic processing. The study of visual object recognition abilities, based on latent variable modeling, provides strong evidence for domain-general mechanisms with neural correlates in visual areas and contributions to many real-world visual problems. The study of ensemble perception includes evidence for interesting individual differences but the structure of abilities is unclear, with a need for multivariate investigation. The study of individual differences in holistic processing has been unable to establish the construct validity of its measures. Each of these areas is at a different stage of understanding relevant underlying abilities, each one helping to illustrate different challenges that may be unfamiliar to experimentalists.